Public History of Education: riflessioni, testimonianze, esperienze - Gianfranco Bandini (Studi e saggi, 2019)
This volume represents the founding act of a proposal for training, didactic, study and research work which aims at enhancing historical knowledge in the field of education and educational professionalism. The contributions intend to highlight the identity and usefulness of history and, in particular, of the history of education, not only for every education level, but for the life of local communities itself. At the same time, the authors aim at suggesting a desirable development of the history of education by adopting a Public History approach. This way, academic knowledge can actually be brought into contact with educational contexts, much more so than it has been done so far, in order to respond, together with other disciplines, to the emerging social needs. The Public History of Education, intended this way, can create new profitable relationships between formal and informal education, between the past and present of educators and teachers, between the world of research, cultural institutes (above all, museums) and society.